Penguatan Kemampuan Profesional Guru Melalui Pengembangan Pembelajaran yang Berpusat pada Peserta Didik di SMK IPTEK Kota Tangerang Selatan - Neng Nurhemah; Muhammad Suheppy; Akhirudin Akhirudin (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
Strengthening teachers' professional competence is a key factor in improving education quality, particularly in implementing student-centered learning. This study aims to analyze efforts to enhance teachers' professional competence through the development of student-centered learning at SMK IPTEK Kota Tangerang Selatan. A qualitative approach with a case study method was used in this research. Data were collected through in-depth interviews with teachers and school policymakers, classroom observations, and document analysis related to lesson planning and evaluation. The findings indicate that strengthening teacher competencies through training, mentoring, and collaborative lesson planning significantly improves their ability to design and implement student-centered learning. This approach also enhances student engagement, critical thinking skills, and independence in the learning process. However, challenges in implementation were identified, including teacher readiness, limited resources, and adaptation to innovative teaching methods. Therefore, continuous teacher professional development, institutional support, and a collaborative learning environment are essential for optimizing the implementation of student-centered learning. Sustained teacher competency enhancement can contribute to improving vocational education quality and preparing students to meet the evolving demands of the workforce.